International trade and economy: A historical perspective - Junior, Carlos Melo de Andrade; Silva, Carlos Gustavo Lopes da (Seven Editora, 2024)
The article discusses the historical evolution of commercial relations throughout human history, from primitive exchanges to the contemporary scenario of complex challenges in global trade relations, including the formation of international institutions such as the World Trade Organization and the importance of international logistics in economic development and the competitiveness of nations. The text highlights the importance of international trade in the development of nations and in fostering good relationships and satisfactory trade relations between nations. The approach methodology is inductive, and the research technique is qualitative bibliographic analysis. The primary objective of this work is to analyze the evolution of commercial relations throughout human history, from the early days of barter to the sophisticated forms of trade today. It will address the crucial phases of this development, from primitive exchanges to complex global trade systems. The results demonstrate that the history of trade is intrinsically linked to the development of humanity, driving economic growth and collaboration between nations. The formation of international institutions has played a fundamental role in fair trade relations and maintaining global peace. International logistics has emerged as a key component in global trade, driving economic development and the competitiveness of nations. The contemporary scenario brings complex challenges, including trade tensions and protectionism, which can negatively affect global trade and economic growth. DOI:https://doi.org/10.56238/sevened2023.006-113